A novel kinematic architecture for portable hand exoskeletons. (May 2016) - Conti, R.; Meli, E.; Ridolfi, A.
Abstract: Basing on strict requirements of portability, low cost and modularity, an assistive device for hand-opening impairment, characterized by an innovative mechanism, has been developed and tested by the authors. This robotic orthosis is designed to be a low-cost and portable hand exoskeleton to assist people with hand-opening impairment in their everyday lives. The mechanism has been especially studied for this kind of applications and presents some interesting features in terms of limited encumbrances and costs. Concerning the hand-opening impairment, the authors have also developed a methodology which, starting from the geometrical characteristics of the patient's hand, properly defines the novel kinematic mechanism that better fits the finger trajectories. The authors have tested and validated the proposed approach by building a functional Hand Exoskeleton System (HES) prototype. The preliminary testing phase of the prototype with a single subject is concluded; currently, a group of subjects is testing the proposed HES methodology in collaboration with a rehabilitation center.